277. Assessment of a Pharmacist-Driven Voriconazole Clinical Practice Guideline in a Children's Hospital. (26th November 2018) - Huppler, Anna; Kissell, Anna; Havens, Peter; Zembles, Tracy
Abstract: Background: The objective of the study was to measure effectiveness of a voriconazole clinical practice guideline (CPG) in a pediatric hospital. An interdisciplinary team was convened to develop a CPG to standardize initial voriconazole dosing, appropriate use and timing of therapeutic drug monitoring (TDM), and dose modifications based on measured drug concentrations. To operationalize the CPG, pharmacists with advanced training in pharmacokinetics were granted authority to order laboratory evaluations and make dose adjustments. Methods: After 6 months, the initial CPG was reviewed and modified to refine TDM recommendations. Adherence to the guideline and ability of the CPG to achieve target voriconazole trough concentrations were assessed before and after the revision. Patients in the analysis included those admitted to a large free-standing children's hospital and receiving voriconazole for confirmed, probable, or presumed fungal infection from April 1, 2015 to December 31, 2016 (25 subjects, median age 10 years). Results: The study showed that the use of TDM increased following implementation of a CPG from 42% to 100% with improved timing of TDM to reflect concentrations drawn at steady state. Of the patients receiving TDM, achievement of voriconazole concentration in the therapeutic range increased from 70% to 100% with the CPG; however, there was no improvement in the time to reach target concentration. We observed an inability of American Academy of Pediatrics-recommended doses to reach target concentration in 53% of patients, with doses based on pharmacist judgement performing as well as published dosing. Conclusion: We conclude that a pharmacist-driven voriconazole CPG improved monitoring and achievement of therapeutic concentrations in our children's hospital. Analysis of effectiveness of our voriconazole CPG in conjunction with pharmacist feedback has been essential to improving patient outcomes and informing future guideline modifications. Disclosures: All authors: No reported disclosures.